1978
DOI: 10.1021/bi00595a024
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance studies of the binding site interactions between 19F-labeled nitrophenyl haptens and specific mouse myeloma immunoglobulin MOPC-315

Abstract: The interactions between MOPC-315, a mouse myeloma protein with specificity for nitrophenyl haptens, and 19F-substituted haptens have been investigated using nuclear magnetic resonance (NMR) spectroscopy. The haptens studied are mono- or dinitrophenyl derivatives of gamma-aminobutyric acid, lysine, or glycine which have trifuoromethyl groups attached to the phenyl rings. Upon binding to immunoglobulin, the 19F nucleus experiences a downfield shift whose magnitude depends on the position of the trifluoromethyl … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

1980
1980
1991
1991

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…The 19 F nucleus is a simple I = 1/2 spin system exhibiting high sensitivity (0.833 relative to 1 H) and frequency dispersion (>10-fold that of 1 H). As a result 19 F is well suited as an observation nucleus in NMR studies of macromolecules too large or too insoluble for multidimensional NMR techniques (Sykes et al, 1974;Pratt & Ho, 1975;Lu et al, 1976;Kooistra & Richards, 1978;Post et al, 1984;Wilson & Dahlquist, 1985;Peerson et al, 1990;Li et al, 1990;Luck & Falke, 1991a,b). We have previously incorporated 5F-Trp into the D-galactose and D-glucose receptor by overexpressing a plasmid containing the receptor gene in the E. coli tryptophan auxotroph W3110 Trp A33 with addition of 5F-Trp to the growth medium (Luck & Falke, 1991a).…”
Section: Use Of 19 F Nmr To Detect Cleft Opening: General Approachmentioning
confidence: 99%
“…The 19 F nucleus is a simple I = 1/2 spin system exhibiting high sensitivity (0.833 relative to 1 H) and frequency dispersion (>10-fold that of 1 H). As a result 19 F is well suited as an observation nucleus in NMR studies of macromolecules too large or too insoluble for multidimensional NMR techniques (Sykes et al, 1974;Pratt & Ho, 1975;Lu et al, 1976;Kooistra & Richards, 1978;Post et al, 1984;Wilson & Dahlquist, 1985;Peerson et al, 1990;Li et al, 1990;Luck & Falke, 1991a,b). We have previously incorporated 5F-Trp into the D-galactose and D-glucose receptor by overexpressing a plasmid containing the receptor gene in the E. coli tryptophan auxotroph W3110 Trp A33 with addition of 5F-Trp to the growth medium (Luck & Falke, 1991a).…”
Section: Use Of 19 F Nmr To Detect Cleft Opening: General Approachmentioning
confidence: 99%
“…Dwek's group demonstrated that the difference between the NMR spectrum of the Fv fragment of the antibody and the NMR spectrum of the Fv complex with dinitrophenyl (DNP) can be used as a fingerprint for the combining site structure (Dower & Dwek, 1979;Dower et al, 1977). Richards and his co-workers used phosphorus and fluorine NMR to study the binding kinetics of several haptens to antibodies (Goetze & Richards, 1978; Kooistra & Richards, 1978). Later…”
mentioning
confidence: 99%
“…(ii) As one moves from the region of slow exchange to the region of intermediate exchange, the two peaks come closer together and coalesce at k0, = l/rB = (& ~rA/2) ( 5 ) under conditions of equal populations of bound and free hapten where PF = PB and rF = rB. (5) As the exchange rate further increases, a single absorption is observed at a chemical shift which is the weighted average of the chemical shift in the two environments [Hap,] and [Ab * Hap] are the concentrations of total hapten in solutions and of hapten bound to antibody, respectively. The observed line width of this absorption is the weighted average of the intrinsic line widths for the bound and free hapten plus further broadening caused by the exchange process itself.…”
Section: Chemical Shift-line Widthmentioning
confidence: 98%
“…(ii) As one moves from the region of slow exchange to the region of intermediate exchange, the two peaks come closer together and coalesce at k0, = l/rB = (& ~rA/2) ( 5 ) under conditions of equal populations of bound and free hapten where PF = PB and rF = rB.…”
Section: Chemical Shift-line Widthmentioning
confidence: 99%